Electric properties of new composite materials based on RGO, nanosized ZnO and Cu nanoparticles. Issue 1 (February 2021) - Martinov, B; Slavov, S; Staneva, A; Dimitrov, D; Mateeva, J
Abstract: Graphene nanostructures combine properties that make them an attractive material for various technical applications. The objective of this study is to obtain a series composites based on Reduced graphene oxide (RGO), nano-sized ZnO and Cu nanoparticles. RGO is synthesized by a modified Hammer's method and chemical reduction after sonication. ZnO nanoparticles are obtained by the Sol-Gel method. The composites' phases and structures are characterized by XRD, SEM, TEM, and EDX analysis. It is shown that ZnO is monophasic with a particle size of 48 nm. A series of composite materials based on RGO, ZnO and Cu nanoparticles is obtained by ultrasonic treatment. Electrical and dielectric properties are measured by Impedance analyser and RLC bridge. For comparison, the conductivity for 100% RGO is 309.513 S/m and for 100 % Cu nanosized is 0.0056 S/m. Therefore, it should be initially concluded that increasing the RGO in the mixture will increase the conductivity, and increasing nanosized Cu will decrease it. The presence of cluster regions in the composites with different conductivity is found: 1) nano grains of conductive copper which are partially or completely surrounded by 2) low-conductivity shells of copper oxide and a minimal number of RGO sheets. The present work shows promising results for future research for the creation of new composite materials with controlled shape and size of copper oxide - RGO clusters. Dielectric measurements for RGO/ZnO composites are made in range from 5 mass% to 100 mass% content of RGO, the composites show variable conductivity. For lower concentration of RGO, selected samples are dielectrics.